Copper-molybdenum metal etching solution as well as preparation method and application thereof

The copper-molybdenum etching solution, with hydrogen peroxide and self-assembled monolayers, addresses etching consistency and adhesion issues in Cu-Mo layers, achieving stable and precise etching for high-resolution displays by controlling etching rates and preventing defects.

CN119710702APending Publication Date: 2025-03-28SHANGHAI SHENGJIAN MICROELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411941068.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The challenge in the metal etching industry is to achieve consistent and high-resolution etching of copper (Cu) and molybdenum (Mo) layers for large liquid crystal display panels, where Cu's low line width is advantageous but its poor adhesion to glass substrates and insulation layers leads to diffusion issues, and the introduction of Mo complicates etching consistency and residue problems.

Method used

A copper-molybdenum metal etching solution is developed, comprising 10.00wt% to 20.00wt% hydrogen peroxide, 1.00wt% to 4.00wt% hydrogen peroxide stabilizer, 1.00wt% to 5.00wt% acidic compound, 0.50wt% to 1.00wt% self-assembled monolayer (SAM) molecules, and 0.10wt% to 2.00wt% corrosion inhibitors, which forms a dense SAM on Cu surfaces to control etching rates and prevent defects.

Benefits of technology

The solution ensures stable and precise etching of Cu-Mo metal layers, preventing defects like corner rounding, recesses, and uneven etching, thereby enhancing etching precision and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710702A_ABST
    Figure CN119710702A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-molybdenum metal etching solution as well as a preparation method and application thereof, and relates to the technical field of etching solutions. Comprising urea peroxide, a urea peroxide stabilizer, an acidic composition, a self-assembled membrane compound, a corrosion inhibitor, a complexing agent and the balance of water. Urea peroxide is used as a main oxidizing agent, an acid composition is used as a main corrosive agent, and a complexing agent and a urea peroxide stabilizer are matched to ensure the use safety in the etching process, so that safe and effective etching of copper and molybdenum metals can be realized. Furthermore, a self-assembled film is generated through a reaction of a self-assembled film compound and a corrosion inhibitor, and the self-assembled film is adsorbed on the surface of the metal oxide oxidized by urea peroxide to control the corrosion rate of the acidic composition, so that the etching precision of the product is ensured, and the problems of chamfering, etching indentation, large unilateral etching variation and the like are avoided; and the stability of the etched taper angle is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of etching liquids, and in particular to a copper-molybdenum metal etching liquid and a preparation method and application thereof. Background Art

[0002] Etching is a technology that uses chemical reactions or physical impact to remove materials from the metal surface, thereby forming patterns or text on the metal surface. It is often used to make products such as circuit boards, metal crafts, nameplates and logos. With the continuous improvement of living standards and scientific and technological levels, the requirements for metal etching in products are getting higher and higher.

[0003] Taking the liquid crystal display panel as an example, as the size of the liquid crystal display panel increases, the metal circuit board is required to meet the electrical requirements while arranging the wires densely, which requires the etched metal circuit board to maintain a good morphology after etching. Compared with traditional aluminum-chromium wiring, copper has a lower line width and is more suitable for the production of high-resolution panels. However, due to the poor adhesion of copper to the glass substrate and the insulating film, it is easy to diffuse into the active layer, so molybdenum and its alloys are usually used as the lower thin film metal of copper for connection. After the introduction of the molybdenum metal layer, the etching consistency of copper and molybdenum and the etching residue problem have become one of the technical problems that need to be solved urgently in this field.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a copper-molybdenum metal etching solution and a preparation method and application thereof.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a copper-molybdenum metal etching solution, which comprises the following components by mass percentage: 10.00wt% to 20.00wt% of urea peroxide; 1.00wt% to 4.00wt% of urea peroxide stabilizer; 1.00wt% to 5.00wt% of an acidic composition; 0.50wt% to 1.00wt% of a self-assembled membrane compound; 0.10wt% to 1.00wt% of a corrosion inhibitor; 0.10wt% to 2.00wt% of a complexing agent, and the remainder is water.

[0008] By using carbamide peroxide as the main oxidant, combining an acidic composition to ensure the etching ability of the metal film, and coordinating a complexing agent and a carbamide peroxide stabilizer to ensure the time stability, service life and etching excellence of the etching process, an effective etching effect on copper and molybdenum metals can be achieved. Further, a self-assembled film can be formed on the surface of the metal copper through the reaction of a self-assembled film compound and a corrosion inhibitor. The self-assembled film has a certain density, and it is adsorbed on the metal surface, which can inhibit metal corrosion, ensure the stability of the etching rate and etching morphology, and avoid problems such as chamfering, etching indentation and large changes in single-sided etching.

[0009] In a second aspect, the present invention provides a method for preparing an etching solution as provided in any of the aforementioned embodiments, comprising uniformly mixing urea peroxide, a urea peroxide stabilizer, an acidic composition, a corrosion inhibitor, a complexing agent and water in proportion, and then adding a self-assembled membrane compound to mix.

[0010] And / or, after adding the self-assembled membrane compound, stirring, mixing and filtering are performed.

[0011] In order to ensure that the components in the etching solution are evenly mixed, the other raw materials are first fully mixed and then the self-assembled membrane compound is added for mixing and dissolution.

[0012] In a third aspect, the present invention provides an application of an etching solution as provided in any of the aforementioned embodiments or an etching solution prepared by the preparation method provided in the aforementioned embodiments in etching copper-molybdenum bimetallic layer materials to meet the product upgrade needs of various display panels or electrical appliances.

[0013] And / or, in the copper-molybdenum bimetallic layer material, the thickness of the copper layer is The thickness of the molybdenum layer is And the molybdenum layer is located under the copper layer.

[0014] The present invention has the following beneficial effects:

[0015] The present invention provides a copper-molybdenum metal etching solution and a preparation method and application thereof. By using carbamide peroxide as a main oxidant, an acidic composition as a main corrosive agent, and coordinating a complexing agent and a carbamide peroxide stabilizer to ensure the safety of the etching process, safe and effective etching of copper-molybdenum metal can be achieved. Further, a self-assembled film is generated by reacting a self-assembled film compound with a corrosion inhibitor, and the self-assembled film is adsorbed on the surface of the metal oxide oxidized by carbamide peroxide to control the corrosion rate of the acidic composition, thereby ensuring the etching accuracy of the product, avoiding problems such as chamfering, etching indentation, and large single-side etching variation, and improving the stability of the cone angle after etching. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 A scanning electron microscope image of the etched product when the Cu ion concentration is 0 ppm during the etching process of the copper-molybdenum metal etching solution provided in Example 3 of the present invention;

[0018] Figure 2 A scanning electron microscope image of a product etched during the etching process of the copper-molybdenum metal etching solution provided in Example 3 of the present invention when the Cu ion concentration is 2000 ppm;

[0019] Figure 3 A scanning electron microscope image of a product etched during the etching process of the copper-molybdenum metal etching solution provided in Example 3 of the present invention when the Cu ion concentration is 4000 ppm;

[0020] Figure 4 A scanning electron microscope image of a product etched during the etching process of the copper-molybdenum metal etching solution provided in Example 3 of the present invention when the Cu ion concentration is 6000 ppm;

[0021] Figure 5 A scanning electron microscope image of the etched product during the etching process of the copper-molybdenum metal etching solution provided in Example 3 of the present invention when the Cu ion concentration is 8000ppm. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0023] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0024] In a first aspect, the present invention provides a copper-molybdenum metal etching solution, which comprises the following components by mass percentage: 10.00wt% to 20.00wt% of urea peroxide; 1.00wt% to 4.00wt% of urea peroxide stabilizer; 1.00wt% to 5.00wt% of an acidic composition; 0.50wt% to 1.00wt% of a self-assembled membrane compound; 0.10wt% to 1.00wt% of a corrosion inhibitor; 0.10wt% to 2.00wt% of a complexing agent, and the remainder is water.

[0025] The present invention uses carbamide peroxide as the main oxidant, combined with an acidic composition to ensure the etching ability of the metal film, and cooperates with a complexing agent and a carbamide peroxide stabilizer to ensure the etching stability, service life and etching excellence of the etching process, so as to achieve an effective etching effect on copper and molybdenum metals. Further, a self-assembled film can be formed on the surface of the metal copper through the reaction of a self-assembled film compound and a corrosion inhibitor. The self-assembled film has a certain density and is adsorbed on the surface of the metal oxide oxidized by carbamide peroxide, so as to inhibit the metal corrosion rate, ensure the stability of the etching rate and the etching morphology, avoid problems such as chamfering, etching indentation and large unilateral etching variation, and improve the stability of the cone angle after etching.

[0026] In an optional embodiment, the pH of the etching solution is 1.5 to 2.1, for example, it can be any value among 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or 2.1, or a range between any two values.

[0027] Controlling the pH of the etching solution within the above range is conducive to ensuring that the etching process proceeds smoothly and that a pattern with a morphology that meets the requirements after etching can be obtained. When the pH value of the etching solution is less than 1.5, on the one hand, the strong acidity of the etching solution will inhibit the reaction of the self-assembled film compound and the corrosion inhibitor, thereby affecting the formation of the self-assembled film and reducing the stability of the self-assembled film adsorbed on the metal surface to be etched; on the other hand, the strong acidity of the etching solution will cause the metal to etch too quickly, and the concentration of metal ions in the etching solution will increase, resulting in a deterioration of the etching morphology. When the pH value of the etching solution is greater than 2.1, the etching rate is significantly reduced due to the weak acidity of the etching solution, and there may be residual etching metal due to uneven etching or metal precipitation due to excessive concentration of metal ions in the etching solution.

[0028] Preferably, the copper-molybdenum metal etching solution provided by the present invention comprises the following components, measured by mass percentage: 12.00wt% to 15.00wt% of urea peroxide; 2.00wt% to 4.00wt% of urea peroxide stabilizer; 2.00wt% to 5.00wt% of acidic composition; 0.50wt% to 0.80wt% of self-assembled membrane compound; 0.30wt% to 0.80wt% of corrosion inhibitor; 0.10wt% to 1.00wt% of complexing agent, and the balance is water.

[0029] By controlling the ratio of urea peroxide, urea peroxide stabilizer, acidic composition, self-assembled film compound, corrosion inhibitor and complexing agent within the above preferred range, it is beneficial to improve the etching accuracy of the etching solution during the etching process of copper and molybdenum metals, and at the same time improve the stability of the cone angle after etching.

[0030] In the copper-molybdenum metal etching solution provided by the present invention, the mass percentage of carbamide peroxide is 10.00wt% to 20.00wt%, for example, it can be any value of 10.00wt%, 11.00wt%, 12.00wt%, 13.00wt%, 14.00wt%, 15.00wt%, 16.00wt%, 17.00wt%, 18.00wt%, 19.00wt% or 20.00wt% or a range value between any two values. Preferably, it is 12.00wt% to 15.00wt%.

[0031] Carbamide peroxide is used as the main oxidant of copper, and its mass percentage is controlled within the above range, so that the etching rate of copper and molybdenum is more stable, and the morphology after etching is more excellent. When the content of carbamide peroxide is lower than 10.00wt%, the ability of the etching solution to oxidize metals decreases, which not only leads to a decrease in etching rate and the easy occurrence of metal residues, but also reduces the metal oxide formed after the oxidation of the etched metal, affecting the complete coverage of the self-assembled film on the surface of the metal oxide, thereby affecting the etching effect, such as uneven etching rate and / or the occurrence of metal residues; when the content of carbamide peroxide is higher than 20.00wt%, the ability of the etching solution to oxidize metals is enhanced, the total etching rate is too fast, and after adding self-assembled film compounds and corrosion inhibitors, the safety of the etching process is unstable.

[0032] In an optional embodiment, the role of the urea peroxide stabilizer is to ensure the stability of the etching solution during the etching process, to avoid excessive decomposition of urea peroxide leading to heat release, thereby affecting the smooth progress of the etching process. Therefore, the urea peroxide stabilizer includes at least one of sodium hexametaphosphate, diethylenetriamine penta (methylene phosphonic acid) and hydroxyethylidene diphosphonic acid. Preferably, sodium hexametaphosphate.

[0033] Further, in the copper-molybdenum metal etching solution provided by the present invention, the mass percentage of the carbamide peroxide stabilizer is 1.00wt% to 4.00wt%, for example, it can be any value of 1.00wt%, 1.50wt%, 2.00wt%, 2.50wt%, 3.00wt%, 3.50wt% or 4.00wt% or a range value between any two values. Preferably, it is 2.00wt% to 4.00wt%.

[0034] By controlling the mass percentage of the urea peroxide stabilizer within the above range, the safety of the etching process can be ensured, and a product with a better etching morphology can be obtained. When the content of the urea peroxide stabilizer is less than 1.00wt%, the safety protection of the etching process is insufficient, which may easily lead to the inability to perform etching; when the content of the urea peroxide stabilizer is higher than 4.00wt%, due to the complexation effect of the stabilizer on metal ions, the excessive content of the stabilizer may cause the etching rate to become faster.

[0035] In an alternative embodiment, the complexing agent includes at least one of ethylenediaminetetraacetic acid, diethylenetriaminetetraacetic acid, and diethylenetriaminepentaacetic acid.

[0036] During the etching process, metal ions will gradually transfer to the etching solution. The chelating agent can complex with the copper ions in the etching solution to form a stable complex, reducing the decomposition effect of copper ions on urea peroxide, avoiding excessive decomposition of urea peroxide, resulting in exothermic explosion, and providing a more stable etching environment.

[0037] In the copper-molybdenum metal etching solution provided by the present invention, the mass percentage of the complexing agent is 0.10wt% to 2.00wt%, for example, it can be any value among 0.10wt%, 0.30wt%, 0.50wt%, 0.70wt%, 0.90wt%, 1.10wt%, 1.30wt%, 1.50wt%, 1.70wt%, 1.90wt% or 2.00wt% or the range value between any two values. Preferably, it is 0.10wt% to 1.00wt%.

[0038] By controlling the mass percentage of the complexing agent within the above range, the etching process is facilitated to proceed smoothly. When the content of the complexing agent is lower than 0.10wt%, as the etching reaction proceeds, the uncomplexed copper ions in the etching solution increase, affecting the service life of the etching solution; when the content of the complexing agent is higher than 2.00wt%, excessive complexing agent will cause the etching speed to become faster and the etching morphology to become worse.

[0039] After being oxidized by carbamide peroxide in the etching solution, the acidic composition, as the main raw material for corroding metal oxides, has a significant impact on the etching effect.

[0040] In an alternative embodiment, the acidic composition includes an organic acid and / or a phosphate. For example, the acidic composition may be an organic acid alone, a phosphate alone, or a mixture of an organic acid and a phosphate.

[0041] The organic acid comprises at least one of malonic acid, formamidinesulfinic acid and meta-chloroperbenzoic acid.

[0042] The phosphate salts include monoammonium phosphate and / or diammonium hydrogen phosphate.

[0043] The main function of organic acid and phosphate is to maintain the pH value of the etching solution in the range of 1.5 to 2.1, to ensure the stability of the etching reaction process, and at the same time to ensure the stability of the quality of the product after etching.

[0044] Preferably, the acidic composition is a composition of an organic acid and a phosphate, wherein the addition of the organic acid can increase the etching rate of the etching solution on copper and molybdenum and reduce metal residues; the phosphate, as a pH buffer, can ensure that the pH of the etching solution is maintained in the range of 1.5 to 2.1 during the entire etching process, so that the sustained release effect of the self-assembled film formed by the self-assembled film compound and the corrosion inhibitor is more balanced with the etching effect, which is beneficial to controlling the etching efficiency and the quality of the etched product.

[0045] Preferably, the mass ratio of the organic acid to the phosphate is (5-10):1, for example, it can be any value among (5:1), (6:1), (7:1), (8:1), (9:1) or (10:1) or a range value between any two values.

[0046] When the mass of organic acid and phosphate is relatively small, the pH of the etching solution may be higher, the etching speed may be slower, and quality problems such as etching residue may be easily generated; when the mass of organic acid and phosphate is relatively large, the pH of the etching solution may be lower, the etching speed may be faster, and quality problems such as inconsistent etching of copper and molybdenum may be caused.

[0047] Further, in the copper-molybdenum metal etching solution provided by the present invention, the mass percentage of the acidic composition is 1.00wt% to 5.00wt%, for example, it can be any value of 1.00wt%, 1.50wt%, 2.00wt%, 2.50wt%, 3.00wt%, 3.50wt%, 4.00wt%, 4.50wt% or 5.00wt% or a range value between any two values. Preferably, it is 2.00wt% to 5.00wt%.

[0048] By controlling the mass percentage of the acidic composition within the above range, the copper and molybdenum metal film layers can be etched simultaneously to maintain a suitable etching rate. When the content of the acidic composition is lower than 1.00wt%, the pH of the etching solution is lower, the etching speed is faster, and it is difficult to control the quality of the etched product; when the content of the acidic composition is higher than 5.00wt%, the pH of the etching solution is higher, the etching speed is slower, and the reaction of the self-assembled film compound and the corrosion inhibitor is also affected.

[0049] After long-term research, the inventors found that in the etching process of copper and molybdenum, the etching rate of molybdenum is always higher than that of copper, which easily leads to quality problems such as undercutting or tailing in the etched product. By adding self-assembled film compounds and corrosion inhibitors, the two react to form a self-assembled film, which has good adsorption to metal oxides. After the metal to be etched contacts the etching solution, it is oxidized by urea peroxide to form metal oxides, so that the self-assembled film can be adsorbed on the surface of the metal to be etched. On the one hand, the corrosion potential of copper is negatively shifted, the etching rate of copper is reduced, and excessive etching of copper is avoided when etching molybdenum, thereby causing quality problems such as tailing; on the other hand, it avoids quality problems such as undercutting caused by premature etching of molybdenum during copper etching. It is beneficial to control the etching rate and etching accuracy of copper and molybdenum, and improves the quality stability of etched products.

[0050] Therefore, in an alternative embodiment, the self-assembled membrane compound includes 3-methoxysalicylaldehyde and / or o-aminobenzaldehyde.

[0051] In an optional embodiment, the corrosion inhibitor includes at least one of 1,2,3-benzotriazole, 1,2,4-triazole, 2-aminobenzimidazole and 5-aminotetrazolyl. Preferably, it is 1,2,3-benzotriazole and / or 2-aminobenzimidazole; more preferably, it is 1,2,3-benzotriazole and 2-aminobenzimidazole. Among them, 2-aminobenzimidazole has better corrosion inhibition performance than other substances, which can further improve the morphology after etching and prevent problems such as chamfering and etching indentation.

[0052] By selecting the raw materials of the self-assembled film compound and the corrosion inhibitor, 3-methoxy salicylaldehyde and / or o-aminobenzaldehyde can react with the corrosion inhibitor to generate a Schiff base compound (-RC=N-). The -C=N- group in the Schiff base compound is very easy to complex with metal ions, thereby forming a self-assembled film with a certain hydrophobic effect on the surface of the metal film layer, shifting the corrosion potential of copper negatively, improving the stability of the etching rate, and at the same time improving the stability of the cone angle after etching.

[0053] Further, in the copper-molybdenum metal etching solution provided by the present invention, the mass percentage of the self-assembled membrane compound is 0.50wt% to 1.00wt%, for example, it can be any value among 0.50wt%, 0.60wt%, 0.70wt%, 0.80wt%, 0.90wt% or 1.00wt% or a range value between any two values. Preferably, it is 0.50wt% to 0.80wt%.

[0054] By controlling the mass percentage of the self-assembled film compound within the above range, the self-assembled film compound and the corrosion inhibitor can undergo a nucleophilic addition reaction, introduce a hydrophobic group and form a self-assembled film. As etching proceeds, the self-assembled film can more effectively control the etching speed, avoiding problems such as chamfering, etching indentation and large unilateral etching variation.

[0055] When the content of the self-assembled membrane compound is less than 0.50wt%, as the metal ion concentration in the etching solution increases, the etching rate becomes significantly faster and the cone angle becomes larger after etching; when the content of the self-assembled membrane compound is greater than 1.00wt%, the etching rate decreases significantly, and even metal residue or precipitation occurs.

[0056] In the copper-molybdenum metal etching solution provided by the present invention, the mass percentage of the corrosion inhibitor is 0.10wt% to 1.00wt%, for example, it can be any value among 0.10wt%, 0.20wt%, 0.30wt%, 0.40wt%, 0.50wt%, 0.60wt%, 0.70wt%, 0.80wt%, 0.90wt% or 1.00wt% or a range value between any two values. Preferably, it is 0.30wt% to 0.80wt%.

[0057] By controlling the mass percentage of the corrosion inhibitor within the above range, it is beneficial to ensure the stability of the metal etching rate, reduce the replacement frequency of the etching solution, and increase the service life of the etching solution. When the content of the corrosion inhibitor is lower than 0.10wt%, the total etching rate of the etching solution is too fast, which reduces the service life of the etching solution; when the content of the corrosion inhibitor is higher than 1.00wt%, the total etching rate is too slow, making it difficult to effectively etch copper and molybdenum.

[0058] In an optional embodiment, the composition comprises, by mass percentage: 15.00 wt% of carbamide peroxide, 3.00 wt% of carbamide peroxide stabilizer, 3.50 wt% of acidic composition, 0.70 wt% of self-assembled membrane compound, 0.50 wt% of corrosion inhibitor, 1.00 wt% of complexing agent, and the balance is water.

[0059] By adopting the etching solution with the above formula, not only can copper and molybdenum two metal elements be etched at the same time, but also as the etching progresses, the metal ions in the etching solution increase, which will not affect the stability of the etching rate. Combined with the formation of self-assembled film, it solves the quality problems such as chamfering, etching indentation and undercutting that may occur in the etched product, which is conducive to improving the product yield.

[0060] In a second aspect, the present invention provides a method for preparing an etching solution as provided in any of the aforementioned embodiments, comprising uniformly mixing urea peroxide, a urea peroxide stabilizer, an acidic composition, a corrosion inhibitor, a complexing agent and water in proportion, and then adding a self-assembled membrane compound to mix.

[0061] Since the solubility of the self-assembled film compound is lower than that of other raw materials, in order to ensure uniform mixing of the components in the etching solution, stable reaction, the formation effect of the self-assembled film, and the etching effect of the etching solution, the self-assembled film compound is added and mixed and dissolved after the other raw materials are fully mixed and dissolved.

[0062] And / or, after adding the self-assembled membrane compound, stirring, mixing and filtering are performed to promote the dissolution and reaction of the self-assembled membrane compound.

[0063] In a third aspect, the present invention provides an application of an etching solution as provided in any of the aforementioned embodiments or an etching solution prepared by the preparation method provided in the aforementioned embodiments in etching a copper-molybdenum bimetallic layer material.

[0064] And / or, in the copper-molybdenum bimetallic layer material, the thickness of the copper layer is The thickness of the molybdenum layer is And the molybdenum layer is located under the copper layer.

[0065] The molybdenum layer serves as a connection layer and an isolation layer for the copper layer, and can be made of pure molybdenum metal or a molybdenum alloy, such as any one of a molybdenum-niobium alloy, a molybdenum-titanium alloy and a molybdenum-titanium-nickel alloy.

[0066] In some embodiments, in a three-electrode system in which the working electrode is a copper sheet, the counter electrode is a platinum sheet, and the reference electrode is a saturated calomel, a 3.5wt% to 5.00wt% sodium chloride solution is used as an electrolyte, an etching solution and a copper-molybdenum bimetallic layer material are added to the electrolyte for etching, and the corrosion potential of copper is less than -0.30V.

[0067] In contrast, when no self-assembled membrane compound is added to the etching solution, the copper-molybdenum bimetallic layer material is etched using the same etching environment (a three-electrode system in which the working electrode is a copper sheet, the counter electrode is a platinum sheet, and the reference electrode is a saturated calomel solution, and a 3.5wt% to 5.00wt% sodium chloride solution is used as the electrolyte), and the corrosion potential of copper is -0.22 to -0.27V.

[0068] Examples and Comparative Examples

[0069] The present application embodiment and comparative example both provide an etching solution, and the raw materials and proportions of the etching solution are shown in the following Tables 1 to 3. It should be noted that S in the first column of Tables 1 to 3 refers to the embodiment, and D refers to the comparative example.

[0070] Except for the components shown in Tables 1 to 3, the remaining composition of the etching solution provided in each embodiment and comparative example is deionized water.

[0071] Table 1 Etching solution formulations of the embodiments and comparative examples (wt%)

[0072]

[0073]

[0074] Table 2 Formulation of etching solution of embodiment and comparative example (wt%)

[0075]

[0076] Table 3 Etching solution formulations of the embodiments and comparative examples (wt%)

[0077]

[0078] Test Example 1

[0079] The etching solutions provided in Examples 1 to 18 and Comparative Examples 1 to 14 were used to etch a plurality of identical copper-molybdenum thin film materials, and the effect on the etching effect of the etching solution was observed as the etching time increased, the copper concentration in the etching solution increased, and the etching active components in the etching solution decreased.

[0080] The etching method is as follows: the amount of etching solution is 10 kg, and the etching is performed after the etching solution temperature reaches 30±0.1℃; the same copper-molybdenum film material is etched, where the copper thickness is Molybdenum thickness is The total etching time is 1.3 times EPD. EPD is the total time during the etching process until all etching of copper and molybdenum is completed. The formation of the etching cone angle can be ensured by controlling the total etching time to 1.3 times EPD.

[0081] After etching, the copper-molybdenum film material was rinsed with water within 2 seconds, and the surface moisture was blown dry. Then, the performance parameters after etching were evaluated by scanning electron microscopy (SEM). The results are shown in Tables 4, 5 and Figure 1 to Figure 5 shown.

[0082] Table 4 Etching cone angle of copper-molybdenum thin film material by etching solutions of various embodiments and comparative examples

[0083]

[0084]

[0085]

[0086] Since the etched pattern has multiple cone angles, the copper-molybdenum thin film materials etched in each embodiment and comparative example are tested respectively, and recorded in Table 4 according to the following evaluation criteria:

[0087] Good: cone angle ≤ 60°;

[0088] Generally: cone angle > 60°;

[0089] ×: The etching solution has a drastic temperature rise or precipitates at this copper concentration and cannot be used or tested safely.

[0090] If each cone angle of each copper-molybdenum thin film material satisfies ≤60°, it is recorded as good, and if at least one cone angle is greater than 60°, it is recorded as fair. As the etching process proceeds, the copper concentration in the etching solution increases, resulting in the inability to smoothly perform etching, which is recorded as ×.

[0091] As can be seen from Table 4, the overall service life of the etching solution provided by the embodiment of the present invention is longer than that of the etching solution of the comparative example. After the copper ion concentration in the etching solution provided by the embodiment gradually increases from 0ppm to 8000ppm, the copper-molybdenum thin film material can be etched, and the etching solution provided by Examples 1, 3, 8, 10, 11 and 14 to 18 is 8000ppm of copper ion concentration, which can still ensure that the cone angle of the product after etching meets the requirements, greatly reducing the replacement frequency of the etching solution and extending the service life of the etching solution. However, most of the comparative examples have the etching process that cannot be carried out due to the gradual increase of the copper ion concentration in the etching solution, so the service life of the etching solution provided by the comparative example is shorter.

[0092] In addition, the overall etching effect (cone angle condition) of the etching solution provided by the embodiment of the present invention is also better than that of the comparative example. All embodiments of the present invention can meet the condition that the cone angle of the etched product is ≤60° at a copper ion concentration of 4000ppm; except for Example 4, the other embodiments can meet the condition that the cone angle of the etched product is ≤60° at a copper ion concentration of 6000ppm, and the product quality is good; and some embodiments (Examples 1, 3, 8, 10, 11 and 14 to 18) still have a cone angle of ≤60° at a copper ion concentration of 6000ppm, and the quality of the etched product meets the requirements. In the comparative example, the etching solution of Comparative Example 5 still has a cone angle of >60° at a copper ion concentration of 0ppm, and the etching effect is general; most of the other comparative examples can only keep the cone angle of the etched product ≤60° at a copper ion concentration of 2000ppm, which is difficult to meet the etching requirements of the product. Compared with Example 3, Comparative Example 11 does not add the self-assembled membrane compound. Its cone angle is greater than 60° when the copper concentration of the etching solution exceeds 2000ppm. Therefore, in order to obtain a product with better etching quality, Comparative Example 11 without adding the self-assembled membrane compound needs to increase the replacement frequency of the etching solution, indicating that the service life of the etching solution provided by Comparative Example 11 is lower than that of the embodiment.

[0093] Table 5 Single-side etching amount of copper-molybdenum thin film material by etching solution in each embodiment and comparative example (μm)

[0094]

[0095]

[0096] "×" in Table 5 means that the etching solution has a sharp rise in temperature or precipitates at this copper concentration and cannot be used and tested safely.

[0097] As can be seen from Table 5, the overall service life of the etching solution provided by the embodiment of the present invention is longer than that of the etching solution of the comparative example. After the copper ion concentration in the etching solution provided by the embodiment gradually increases from 0ppm to 8000ppm, the copper-molybdenum thin film material can be etched, and the unilateral etching amount of copper changes less, indicating that the etching performance of the etching solution provided by the embodiment of the present invention is more stable in the entire etching process, and will not be affected by the increase in the concentration of metal ions and fluctuate in a large range. However, most of the comparative examples have the etching process that cannot be carried out due to the gradual increase in the copper ion concentration in the etching solution, indicating that the etching stability of the etching solution provided by the comparative example is worse. In addition, although comparative examples 4, 8, 10 and 11 can still be etched at a copper ion concentration of 8000ppm, the unilateral etching amount of the products etched by the etching solutions of the above-mentioned comparative examples varies greatly, which also indicates that the etching solution provided by the above-mentioned comparative examples is greatly affected by the content of metal ions and has poor etching stability. In addition, comparative example 11 does not add self-assembled membrane compounds compared to Example 3, and its unilateral etching amount varies more than Example 3, and the etching stability is relatively poor.

[0098] Figure 1 to Figure 5 The etching effect of the etching solution provided in Example 3 of the present invention on the copper-molybdenum thin film material at different copper ion concentrations is demonstrated. The cone angle of the copper-molybdenum thin film material after etching is 40 to 43°, and the cone angle is straight and not bent, and the etching effect is very good.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A copper-molybdenum metal etching solution, characterized in that: The copper-molybdenum metal etching solution comprises the following components by mass percentage: 10.00wt% to 20.00wt% of urea peroxide; 1.00wt% to 4.00wt% of urea peroxide stabilizer; 1.00wt% to 5.00wt% of acidic composition; 0.50wt% to 1.00wt% of self-assembled membrane compound; 0.10wt% to 1.00wt% of corrosion inhibitor; 0.10wt% to 2.00wt% of complexing agent, and the balance is water.

2. The etching solution according to claim 1, characterized in that The pH of the etching solution is 1.5-2.

1.

3. The etching solution according to claim 1, characterized in that The self-assembled membrane compound includes 3-methoxy salicylaldehyde and / or o-aminobenzaldehyde.

4. The etching solution according to claim 1, characterized in that The corrosion inhibitor includes at least one of 1,2,3-benzotriazole, 1,2,4-triazole, 2-aminobenzimidazole and 5-aminotetrazolyl.

5. The etching solution according to claim 1, characterized in that Also includes at least one of the following: (a) the complexing agent comprises at least one of ethylenediaminetetraacetic acid, diethylenetriaminetetraacetic acid and diethylenetriaminepentaacetic acid; (b) The urea peroxide stabilizer comprises at least one of sodium hexametaphosphate, diethylenetriamine penta (methylene phosphonic acid) and hydroxyethylidene diphosphonic acid.

6. The etching solution according to claim 1, characterized in that The acidic composition includes an organic acid and / or a phosphate; The organic acid comprises at least one of malonic acid, formamidinesulfinic acid and meta-chloroperbenzoic acid; The phosphate includes diammonium phosphate and / or diammonium hydrogen phosphate.

7. The etching solution according to claim 6, characterized in that: The acidic composition is a composition of an organic acid and a phosphate, and the mass ratio of the organic acid to the phosphate is (5-10):

1.

8. The etching solution according to any one of claims 2 to 7, characterized in that Calculated by mass percentage, the composition comprises: 15.00 wt% of carbamide peroxide, 3.00 wt% of carbamide peroxide stabilizer, 3.50 wt% of acidic composition, 0.70 wt% of self-assembled membrane compound, 0.50 wt% of corrosion inhibitor, 1.00 wt% of complexing agent, and the balance is water.

9. A method for preparing an etching solution as claimed in any one of claims 1 to 8, characterized in that: The method comprises mixing the carbamide peroxide, the carbamide peroxide stabilizer, the acidic composition, the corrosion inhibitor, the complexing agent and the water in a uniform proportion, and then adding the self-assembled membrane compound to mix; And / or, after adding the self-assembled membrane compound, stirring, mixing and filtering are performed.

10. Use of the etching solution according to any one of claims 1 to 8 or the etching solution prepared by the preparation method according to claim 9 in etching a copper-molybdenum bimetallic layer material; And / or, in the copper-molybdenum bimetallic layer material, the thickness of the copper layer is The thickness of the molybdenum layer is And the molybdenum layer is located under the copper layer.